Recent Advances in Information and Communication Technology 2017 Proceedings of the 13th International Conference on Computing and Information Technology (IC2IT) - Meesad, Phayung; Sodsee, Sunantha; Unger, Herwig; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book includes selected contributions related to big data and data networking, presented at the 13th International Conference on Computing and Information Technology (IC2IT), which was held at the Arnoma Grand Hotel Bangkok, Thailand, July 6-7, 2017. The aim of the conference was to present emerging algorithms, methods and technologies with a high degree of originality, novelty and innovation addressing the conference theme `Mastering Data and Networking'. Section 1 and 2 discuss various aspects of data mining and corresponding applications. Section 3 focuses on speed and overhead networking optimisation problems, as well as energy problems of autonomous systems, which are becoming increasingly important. The key to addressing these problems is properly determining critical parameters. Section 4 sheds light on natural language processing, including extraction of trends and popularity and recognition of emotions as well as classic topics such as detection and classification.
Applying Stochastic Evolutionary Algorithm for Correlation Control in Monte Carlo Simulation -- A Hybrid of Fractal Code Descriptor and Harmonic Pattern Generator for Improving Speech Recognition of Diﬀerent Sampling Rates -- Software Size Estimation in Design Phase Based on MLP Neural Network -- Knee Implant Orientation Estimation for X-Ray Images Using Multiscale Dual Filter and Linear Regression Model -- Pseudo-Ranging Based on Round-Trip Time of Bluetooth Low Energy Beacons -- Android IR - Full-text Search for Android -- Business Popularity Analysis from Twitter.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence